Why does rangeland integration by transfer fail to overcome the tragedy of anticommons? - Lianhua Chasu; Wenjun Li; Yu Mu (Ambio, 2023)
In China, rangeland fragmentation leads to the problems of anticommons, in terms of livestock production and ecological conditions. As the countermeasure, rangeland use right transfer has been encouraged by the governments recently, which aims to integrate the fragmented rangelands by lease. Can transfer overcome the problems of anticommons? We addressed this question through a case study in Inner Mongolia, by comparing livelihoods and ecological conditions between the households with lease-in pastures and those without practicing transfer. We found that though transfer could make the livelihoods of lease-in households with larger rangeland better-off in weather good years, but worse-off in drought years; and the over grazing was intensified on the transferred pastures. We concluded that the transfer may not be able to fundamentally overcome the problems of anticommons. We argued that spatial anticommons and right anticommons are interrelated to each other, rather than two juxtaposed types as defined by anticommons scholars.